One-pot synthesis of porous g-C3N4 nanomaterials with different morphologies and their superior photocatalytic performance. (June 2018) - Fei, Ban; Tang, Yuwei; Wang, Xiuying; Dong, Xiaoli; Liang, Jing; Fei, Xu; Xu, Longquan; Song, Yu; Zhang, Feng
Graphical abstract: Highlights: g-C3 N4, liking a yolk-shell cake, was prepared. The shell region is porous nanosheets and the yolk region is hollow particles. The surface area and pore volume of two types of g-C3 N4 could be controlled. The as-prepared porous g-C3 N4 nanomaterials exhibit improved photocatalytic activity. Abstract: Graphitic carbon nitride (g-C3 N4 ), liking a yolk-shell cake, was successfully prepared via a gas-bubble template method with the assistance of NH4 Cl. In this special structure, the shell region consists of numerous thin sheets with rich porosity, while the yolk region consists of a lot of cross-linked large hollow particles. The formation mechanism of yolk-shell structure was investigated via adjusting the mass ratio of NH4 Cl to melamine, and calcination temperature. The surface area and pore volume of the two types of porous g-C3 N4 nanomaterials significantly depend on the mass ratio of NH4 Cl to melamine in a certain extent. The as-prepared porous g-C3 N4 nanomaterials exhibit improved photocatalytic activity compared to bulk g-C3 N4 . Moreover, the porous thin sheets in shell region possess larger specific surface area, higher light utilization, higher charge separation and transfer efficiency, than the hollow particles in yolk region, leading to the superior photocatalytic performance. We believe that this simple, economical, and nontoxic approach for the preparation of g-C3 N4 nanomaterials opens new possibilities for scalable synthesis of g-C3 N4 -based materials with more controllable structures.